The Reconstruction of a Javanese Civilization Cultural Landscape in 8 AD based on Canggal Inscription in Gendol Hill Complex, Magelang, Central Java - Niken Wirasanti; Helmi Murwanto (Faculty of Geography, Universitas Gadjah Mada, 2020)
The research took place in the Gendol Hill complex, Magelang, Central Java. One of the peaks in the hills complex is Mount Wukir, where a Canggal Inscription was found. The Canggal Inscription mentions an area named Java, rich in agricultural products with many sacred buildings. The term Javanese refers to an area of Gendol Hill complex, which is part of the Kedu–Central Java region. This paper aims to 1) interpret the cultural landscape of the Gendol Hill complex, 2) reconstruct the spatial structure (layout), and its utilization as a settlement area for Javanese society in the 8th century. This paper interprets the Canggal Inscription and collates information about the potential of both biotic and non-biotic resources. Data processing is conducted through inductive–explanatory analysis. The results suggest that the Cultural Landscape of Gunung Wukir Temple was in a place protecting it from disaster. The complex was protected by Gendol Hills, acting as a barrier against volcanic eruptions from Mount Merapi. Gendol Hill complex was located in an environment that flourished with both biotic and non-biotic resources. The community cultivated its alluvial plains and established settlements in this area. The denuded structural hills were also perceived as sacred spaces to erect temples with natural resources close by such as andesite rocks available from rivers around the hills.